1992
DOI: 10.1038/bjc.1992.304
|View full text |Cite
|
Sign up to set email alerts
|

Mdr1/P-glycoprotein, topoisomerase, and glutathione-S-transferase π gene expression in primary and relapsed state adult and childhood leukaemias

Abstract: Summary In a variety of adult and childhood leukaemia cell samples collected at different states of the disease, we analysed in a series of sequentially performed slot-blot or Northern-blot hybridisation experiments the expression of genes possibly involved in multiple drug resistance (MDR) (mdrl/P-glycoprotein, DNA topoisomerase II, glutathione-S-transferase x), and the expression of the DNA topoisomerase I and histone 3.1 genes. Occasionally, P-glycoprotein gene expression was additionally examined by indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 39 publications
(42 reference statements)
2
39
0
1
Order By: Relevance
“…These results show that analysis of TOP2A gene at the RNA level is as sensitive as DNA analysis. However, as reported in previous studies, 43,45 we also found large interpatient variations in TOP2A gene expression levels, suggesting that in addition to a simple increase in TOP2A gene copy number, transcriptional and/or post-transcriptional regulation mechanisms might also be implicated in the increased expression of TOP2A gene in ALL cells.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…These results show that analysis of TOP2A gene at the RNA level is as sensitive as DNA analysis. However, as reported in previous studies, 43,45 we also found large interpatient variations in TOP2A gene expression levels, suggesting that in addition to a simple increase in TOP2A gene copy number, transcriptional and/or post-transcriptional regulation mechanisms might also be implicated in the increased expression of TOP2A gene in ALL cells.…”
Section: Discussionmentioning
confidence: 47%
“…This result confirms previous reports tending to show lower TOP2A gene expression levels in primary AML compared to human Tlymphoblastoid cell lines as controls. 43,46 In our cohort of ALL patients, we also identified a small population of children, around 20%, in which TOP2A gene is not amplified or overexpressed and which, remarkably, tends to correspond to most of the VHR patients exhibiting glucocorticoid resistance. This information, which can be rapidly and easily available at the day of diagnosis through the molecular analysis of TOP2A gene, represents a complementary and independent factor that can be useful for a better and faster characterization of VHR patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its physiological function GST-i expression was found in all samples at a low level so that only patients with moderate or intensive staining were considered to be positive for GST-7c overexpression. Gekeler et al (1992) reported moderate GST levels in patients with the initial stage of ALL and with relapsed ALL at the mRNA levels when compared with the cell line CCRF-CEM.…”
Section: Discussionmentioning
confidence: 99%
“…Gekeler et al, 1992;Ishikawa et al, 1993;Beck et al, 1994;Kaufmann et al, 1994;Larsson et al, 1994;McKenna et al, 1994). However, recently more information has become available on Topo-II levels in solid tumours or in primary cultures of solid tumours (e.g.…”
Section: Discussionmentioning
confidence: 99%